Violência sexual incestuosa: uma análise psicanalítica sobre as marcas traumáticas na família - Rodrigues, Maiza dos Santos (2022)
This study aimed to analyze traumatic marks left by the incestuous cycle in this family and to reflect about the analyst's performance in the position of witness to the traumatic. More specifically, interventions were sought in the complexity of trauma as a phenomenon outside from the representative capacity. With this approach, through individual and family consultations, substantial elements emerged and that configured the inscription of trauma in the family scene. Methodologically, the research involved the assistance of a mother and a daughter who were victims of sexual violence at childhood and adolescence. The analysis of the contents was anchored in psychoanalysis and the function and interpretative construction enabled the elaboration of transgenerational elements and their resonances. The following elements of analysis were evidenced: denial, trauma entrenchment, transgenerationality, and the manifestations of pain and suffering. The consultations based on Freudian and Ferenczian psychoanalytic precepts provided the edge of a listening characterized by the tripod of “witnessing, interpreting, and making possible”. The transferential relations provided conditions for traumatic remembrances, the creation of sustainable memories, and the recreation of bonds between mother and daughter. The research highlighted the importance of the third subject in violent scenes, in this case, the analyst, where his function unfolds in the challenge of legitimizing the suffering, mediating its resonances and pointing to the gaps in life that still exist.